Fibers, molded bodies, methods for disposing of fibers, and methods for disposing of molded bodies

Xylylenediamine-based polyamide resin with cobalt salt enhances biodegradability and strength in fibers, addressing the limitations of conventional polyamide resins for environmental applications.

JP7615632B2Active Publication Date: 2025-01-17MITSUBISHI GAS CHEM CO INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020193582
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-20
Publication Date
2025-01-17
Estimated Expiration
2040-11-20

AI Technical Summary

Technical Problem

Polyamide resin fibers lack both biodegradability and high strength, making them impractical for environmental conservation efforts.

Method used

Using a xylylenediamine-based polyamide resin with a cobalt salt, where 50 mol% or more of the diamine-derived structural units are derived from xylylene diamine and 50 mol% or more of the dicarboxylic acid-derived units are from α,ω-linear aliphatic dicarboxylic acids, with a cobalt content of 10 to 2000 ppm, to enhance biodegradability and maintain strength.

Benefits of technology

The fibers exhibit excellent biodegradability, achieving a 10% or more degradation after 90 days in compost conditions while maintaining high strength, suitable for applications like fishing nets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615632000001
    Figure 0007615632000001
  • Figure 0007615632000002
    Figure 0007615632000002
Patent Text Reader

Abstract

To provide a fiber using a polyamide resin and having excellent biodegradability and high strength, a molding, a method for disposing of the fiber, and a method for disposing of the molding.SOLUTION: The fiber contains a polyamide resin and a cobalt salt. The polyamide resin contains a xylylenediamine-based polyamide resin containing a diamine-derived constituent unit and a dicarboxylic acid-derived constituent unit, wherein 50 mol% or more of the diamine-derived constituent unit is derived from xylylenediamine and 50 mol% or more of the dicarboxylic acid-derived constituent unit is derived from a C8-22 α,ω-linear aliphatic dicarboxylic acid.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fibers, molded articles, methods for disposing of fibers, and methods for disposing of molded articles, and in particular to highly biodegradable fibers and the like that use polyamide resin. [Background technology]

[0002] The use of polyamide resins in fibers has been under consideration for some time. For example, Patent Document 1 discloses a monofilament containing a polyamide resin, the polyamide resin containing units derived from ε-caprolactam and / or ε-aminocaproic acid (hereinafter also referred to as "unit 1"), units derived from adipic acid (hereinafter also referred to as "unit 2"), and units derived from hexamethylenediamine (hereinafter also referred to as "unit 3"), and the proportion of units 1 is more than 60 mass% and less than 80 mass% of the total of units 1, 2, and 3. Furthermore, Patent Document 2 discloses polyamide filaments containing a polyamide resin obtained by polycondensation of an aliphatic diamine containing pentamethylenediamine as a main component and a dicarboxylic acid containing adipic acid as a main component. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2016-223037 A [Patent Document 2] JP 2010-281027 A Summary of the Invention [Problem to be solved by the invention]

[0004] As described above, polyamide resins are used in fibers (filaments), but as part of efforts to protect the environment in recent years, there is a demand for polyamide resin fibers with biodegradability. However, even if a fiber has excellent biodegradability, it is not very practical if it has poor strength. The present invention aims to solve such problems, and to provide a fiber using a polyamide resin that is highly biodegradable and has high strength, a molded body, a method for disposing of the fiber, and a method for disposing of the molded body. [Means for solving the problem]

[0005] In view of the above problems, the present inventors have conducted research and found that the above problems can be solved by using a specific xylylenediamine-based polyamide resin as a fiber raw material and blending a cobalt salt therein. Specifically, the above problems were solved by the following means. <1> Contains polyamide resin and cobalt salt, The polyamide resin contains diamine-derived structural units and dicarboxylic acid-derived structural units, and 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms, comprising a xylylenediamine-based polyamide resin. <2> The mass ratio of the xylylenediamine structure in the xylylenediamine-based polyamide resin is 20 to 70 mass%. <1> Here, the mass ratio of the xylylenediamine structure is a value calculated from [(mass of the xylylenediamine structure in the polyamide resin) / (mass of the entire polyamide resin)]×100. <3> The α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms includes an α,ω-linear aliphatic dicarboxylic acid having 11 to 22 carbon atoms. <1> or <2> The fiber described in <4> The α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms includes 1,12-dodecanedioic acid. <1> or <2> The fiber described in <5> the cobalt salt comprises a carboxylate of cobalt; <1> ~ <4> 13. The fiber according to claim 12, <6> The cobalt salt comprises cobalt stearate. <1> ~ <4> 13. The fiber according to claim 12, <7> The content of cobalt atoms in the cobalt salt is 10 to 2000 ppm by mass relative to 100 parts by mass of the xylylenediamine-based polyamide resin. <1> ~ <6> 13. The fiber according to claim 12, <8> It is biodegradable, <1> ~ <7> 13. The fiber according to claim 12, <9> The fiber has a biodegradability of 10% or more after being stored for 90 days in a compost environment at 58±2°C and 100% relative humidity. <1> ~ <8> Here, the degree of biodegradation (%) is [(total amount of CO2 generated during storage for 90 days in a compost environment) / (theoretical amount of carbon dioxide generated calculated from the composition formula)]×100. <10> <1> ~ <9> A molded article formed from the fiber according to any one of claims 1 to 5. <11> The molded body is a fishing net. <10> The molded article according to claim 1. <12> <1> ~ <9> A method for disposing of fibers, comprising biodegrading the fibers described in any one of the above. <13> <10> or <11> 2. A method for disposing of a molded article, comprising biodegrading the molded article according to claim 1. Effect of the Invention

[0006] According to the present invention, it is possible to provide a fiber using a polyamide resin, which has excellent biodegradability and high strength, a molded article, a method for disposing of the fiber, and a method for disposing of the molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. In this specification, ppm means ppm by mass.

[0008] The fiber of the present embodiment is characterized in that it contains a polyamide resin and a cobalt salt, the polyamide resin contains diamine-derived structural units and dicarboxylic acid-derived structural units, 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms, and contains a xylylenediamine-based polyamide resin. By adopting such a constitution, a fiber having excellent biodegradability and high strength can be obtained. The reason for this is presumed to be as follows. For example, if the resin is left in a compost environment for a long period of time to biodegrade, microorganisms act on the resin and reduce the molecular weight of the resin. As a result, microorganisms can easily penetrate further into the resin, and biodegradation progresses, decomposing it into oligomers, monomers, and even further low molecules. However, polyamide resins generally have strong amide bonds and are usually crystalline resins, so they are not easily affected by microorganisms and are less likely to reduce in molecular weight. Therefore, polyamide resins are less likely to be decomposed by microorganisms. In this embodiment, it was speculated that by using a specific xylylenediamine-based polyamide resin as the polyamide resin, the NH2-CH2-benzene ring site of xylylenediamine is oxidized and decomposed by cobalt, and is cleaved between the benzyl site and NH2. As a result, it is speculated that the molecular weight reduction of the xylylenediamine-based polyamide resin is promoted, and biodegradation can be promoted. Furthermore, the fiber of this embodiment maintains the strength that polyamide resin fibers inherently have before biodegradation. The fibers of this embodiment will be described in detail below.

[0009] <Polyamide resin> The fiber of the present embodiment contains a xylylenediamine-based polyamide resin. The xylylenediamine-based polyamide resin in the present embodiment is a polyamide resin that contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine, and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms. By using such a xylylenediamine-based polyamide resin and further blending a cobalt salt, a fiber having excellent biodegradability while maintaining the inherent strength of the fiber can be obtained.

[0010] In the xylylenediamine-based polyamide resin, 50 mol % or more of the diamine-derived constitutional units are derived from xylylenediamine, preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 99 mol % or more. The upper limit may be 100 mol %.

[0011] Xylylenediamine preferably contains 0-100 mol% metaxylylenediamine and 0-100 mol% paraxylylenediamine, more preferably contains 0-90 mol% metaxylylenediamine and 10-100 mol% paraxylylenediamine, and even more preferably contains 0-80 mol% metaxylylenediamine and 20-100 mol% paraxylylenediamine. By containing paraxylylenediamine, biodegradability tends to be further improved. In addition, in xylylenediamine, the total of metaxylylenediamine and paraxylylenediamine preferably accounts for 95 mol% or more, more preferably 99 mol% or more, and even more preferably 100 mol%.

[0012] Diamine components other than xylylenediamine include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine; 1,3-bis(aminomethyl)cyclohexane; 1,4-bis(aminomethyl)cyclohexane; Examples of the diamines include alicyclic diamines such as bis(4-aminocyclohexyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0013] In the xylylenediamine-based polyamide resin, 50 mol % or more of the dicarboxylic acid-derived constitutional units are derived from α,ω-linear aliphatic dicarboxylic acids having 8 to 22 carbon atoms, preferably 70 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 99 mol % or more. The upper limit may be 100 mol %. The number of carbon atoms in the α,ω-straight-chain aliphatic dicarboxylic acid having 8 to 22 carbon atoms is preferably 10 or more, more preferably 11 or more, and even more preferably 12 or more. By making the number of carbon atoms equal to or more than the lower limit, the compound tends to be more susceptible to biodegradation by microorganisms. Furthermore, the number of carbon atoms in the α,ω-straight-chain aliphatic dicarboxylic acid having 8 to 22 carbon atoms is preferably 21 or less, and preferably 20 or less. By making the number of carbon atoms equal to or less than the upper limit, the compound tends to be more susceptible to hydrophilicity and more susceptible to decomposition by microorganisms. The number of carbon atoms in the α,ω-straight-chain aliphatic dicarboxylic acid having 8 to 22 carbon atoms is preferably 10 or 12, and more preferably 12. Specific examples of the α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms include suberic acid, azelaic acid, sebacic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,13-tridecanedioic acid, 1,14-tetradecanedioic acid, 1,15-pentadecanedioic acid, 1,16-hexadecanedioic acid, 1,17-heptadecanedioic acid, 1,18-octadecanedioic acid, 1,19-nonadecanedioic acid, 1,20-eicosane diacid, 1,21 Examples of the α,ω-straight chain aliphatic dicarboxylic acid having 8 to 22 carbon atoms include 1,12-dodecanedioic acid and 1,22-docosane diacid, and more preferably sebacic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, 1,16-hexadecanedioic acid, 1,18-octadecanedioic acid, 1,20-eicosane diacid, 1,21-heneicosane diacid, 1,22-docosane diacid, 1,14-tetradecanedioic acid, 1,16-hexadecanedioic acid, 1,18-octadecanedioic acid, eicosane diacid, and docosane diacid. When the α,ω-straight chain aliphatic dicarboxylic acid having 8 to 22 carbon atoms is 1,12-dodecanedioic acid, the above-mentioned effect is particularly remarkable.

[0014] Examples of dicarboxylic acid components other than α,ω-linear aliphatic dicarboxylic acids having 8 to 22 carbon atoms include α,ω-linear aliphatic dicarboxylic acids having 7 or less carbon atoms, such as adipic acid, phthalic acid compounds, such as isophthalic acid, terephthalic acid, and orthophthalic acid, and naphthalenedicarboxylic acids, such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid, and these can be used alone or in combination of two or more.

[0015] Incidentally, "including diamine-derived structural units and dicarboxylic acid-derived structural units" means that at least a part of the amide bonds constituting the xylylenediamine-based polyamide resin is formed by the bond between dicarboxylic acid and diamine, and further, other sites such as terminal groups may be included in addition to the dicarboxylic acid-derived structural units and diamine-derived structural units. In addition, repeating units having amide bonds not derived from the bond between dicarboxylic acid and diamine, and trace amounts of impurities may also be included. Specifically, in addition to the diamine component and dicarboxylic acid component, lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acids such as aminocaproic acid and aminoundecanoic acid can also be used as copolymerization components as components constituting the xylylenediamine-based polyamide resin, as long as the effects of this embodiment are not impaired. In this embodiment, preferably 90% by mass or more of the xylylenediamine-based polyamide resin, more preferably 95% by mass or more, and even more preferably 98% by mass or more are diamine-derived structural units or dicarboxylic acid-derived structural units.

[0016] The polyamide resin used in the present embodiment preferably has a mass ratio of xylylenediamine structure of 20 to 70 mass%. This configuration allows the resin to have a low molecular weight and the biodegradability of the decomposition products to be improved in a well-balanced manner. Here, the mass ratio of the xylylenediamine structure is a value calculated from [(mass of the xylylenediamine structure in the polyamide resin) / (mass of the entire polyamide resin)]×100. The xylylenediamine structure refers to the portion represented by "-HN-CH2-benzene ring-CH2-NH-". The lower limit of the mass ratio of the xylylenediamine structure is preferably 25% by mass or more, more preferably 28% by mass or more, even more preferably 30% by mass or more, and may be 35% by mass or more, and particularly 40% by mass or more. By making it equal to or more than the lower limit, the starting points of decomposition increase, and low molecular weight components that are more susceptible to biodegradation tend to be generated. In addition, the upper limit of the mass ratio of the xylylenediamine structure is preferably 60% by mass or less, more preferably 55% by mass or less, even more preferably 50% by mass or less, and even more preferably 48% by mass or less. By making it equal to or less than the upper limit, the xylene skeleton that is less susceptible to biodegradation decreases, and the biodegradability of the resin as a whole tends to be improved.

[0017] The content of the xylylenediamine-based polyamide resin in the fiber of this embodiment is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 99% by mass or more. By making it equal to or more than the lower limit, the strength of the fiber is more effectively achieved. The upper limit is the amount at which all components other than the cobalt salt are xylylenediamine-based polyamide resin. The fiber of the present embodiment may contain only one type of xylylenediamine-based polyamide resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0018] The fibers of the present embodiment may or may not contain a polyamide resin other than the xylylenediamine-based polyamide resin. The other polyamide resin may be one or more of an aliphatic polyamide resin, an alicyclic polyamide resin, a semi-aromatic polyamide resin, etc., with an aliphatic polyamide resin and an alicyclic polyamide resin being preferred, and an aliphatic polyamide resin being more preferred. Specific examples of the other polyamide resins include polyamide 4, polyamide 6, polyamide 11, polyamide 12, polyamide 46, polyamide 66, polyamide 6 / 66, polyamide 610, polyamide 612, polyamide 6T, polyamide 6 / 6T, polyamide 66 / 6T, polyamide 6I, polyamide 66 / 6I / 6, polyamide 66 / 6I, polyamide 6T / 6I, polyamide 6T / 12, polyamide 66 / 6T / 6I, polyamide 9T, polyamide 9I, polyamide 9T, 9I, polyamide 10T, 1,3-BAC10I (a polyamide resin composed of 1,3-bisaminomethylcyclohexane, sebacic acid, and isophthalic acid), and 1,4-BAC10I (a polyamide resin composed of 1,4-bisaminomethylcyclohexane, sebacic acid, and isophthalic acid), and polyamide 6 and / or polyamide 66 are preferred. When these other polyamide resins are contained, the content thereof in the fibers is preferably 5 to 15% by mass.

[0019] <Cobalt salts> The fiber of the present embodiment contains a cobalt salt. By containing the cobalt salt, biodegradation of the fiber of the present embodiment is promoted when the fiber is placed in a compost environment, etc. In particular, the cobalt salt hardly has any adverse effect on the xylylenediamine-based polyamide resin before being placed in a compost environment, and therefore is preferable in that it is unlikely to impair the inherent performance (particularly strength) of the fiber when the fiber is used. The type of cobalt salt is not particularly limited, and may be either a divalent salt or a trivalent salt, with a divalent salt being preferred. The cobalt salt is preferably a cobalt carboxylate, since the use of a carboxylate tends to more effectively promote the reduction in molecular weight due to oxidative decomposition at the benzyl position. In the case of a cobalt carboxylate, the carboxylic acid is preferably an aliphatic carboxylic acid. The aliphatic carboxylic acid is not particularly specified because it does not significantly affect the oxidative decomposition behavior of the resin by cobalt, but either a linear or branched aliphatic carboxylic acid can be preferably adopted, and a linear aliphatic carboxylic acid is more preferable. The carbon number of the aliphatic carboxylic acid is not particularly specified because it does not significantly affect the oxidative decomposition behavior of the resin by cobalt, but it is preferably 2 or more, may be 10 or more, and is preferably 40 or less, more preferably 30 or less, and even more preferably 24 or less. In particular, an aliphatic dicarboxylic acid having an even number of carbon atoms is preferable. Specific examples of aliphatic carboxylic acids include acetic acid, neodecanoic acid, lauric acid, neodecanoic acid, myristic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, and melissic acid. From the viewpoint of physical properties, acetic acid, neodecanoic acid, and stearic acid are preferred, and stearic acid is more preferred. In this embodiment, the cobalt salt is preferably cobalt stearate. 17 H 35 COO)2Co is preferred.

[0020] The content of cobalt atoms in the cobalt salt (preferably cobalt stearate) in the resin of this embodiment is preferably 10 mass ppm or more, more preferably 50 mass ppm or more, and even more preferably 80 mass ppm or more, relative to 100 parts by mass of the xylylenediamine-based polyamide resin. By making it equal to or more than the lower limit, the polyamide resin tends to be easily decomposed to a molecular weight that is easily biodegradable. In addition, the content of cobalt atoms in the cobalt salt (preferably cobalt stearate) in the resin of this embodiment is preferably 2000 mass ppm or less, more preferably 1800 mass ppm or less, even more preferably 1500 mass ppm or less, even more preferably 1200 mass ppm or less, even more preferably 1000 mass ppm or less, and even more preferably 800 mass ppm or less. By making it equal to or less than the upper limit, deterioration and poor appearance during preparation of the polyamide resin tend to be effectively suppressed. The fibers of the present embodiment may contain only one type of cobalt salt, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0021] <Other ingredients> The fiber of this embodiment may contain other components other than the polyamide resin and the cobalt salt, as long as the purpose and effect of this embodiment are not impaired. Specific examples of the other components include thermoplastic resins other than polyamide resins, antioxidants, heat stabilizers, hydrolysis resistance improvers, weathering stabilizers, matting agents, UV absorbers, nucleating agents, plasticizers, dispersants, flame retardants, antistatic agents, coloring inhibitors, gelling inhibitors, colorants, release agents, surface activators, dyes, etc. For details of these, refer to the descriptions in paragraphs 0130 to 0155 of Japanese Patent No. 4894982, the descriptions in paragraph 0021 of Japanese Patent Publication No. 2010-281027, and the descriptions in paragraph 0036 of Japanese Patent Publication No. 2016-223037, the contents of which are incorporated herein by reference. Examples of thermoplastic resins other than polyamide resins include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polycarbonate resins, polyoxymethylene resins, polyether ketones, polyether sulfones, thermoplastic polyether imides, etc. The fiber of this embodiment can be configured to be substantially free of thermoplastic resins other than polyamide resins. "Substantially free" means, for example, that the content of thermoplastic resins other than polyamide resins in the fiber of this embodiment is 5% by mass or less of the mass of the polyamide resin. The fibers of this embodiment may contain fillers such as glass fibers, carbon fibers, etc., but preferably do not substantially contain any fillers. For example, "substantially does not contain any fillers" means that the amount of fillers mixed is 3% by mass or less of the fibers of this embodiment. The fiber of the present embodiment may also be configured to be substantially free of plasticizers (e.g., aromatic ester compounds). Substantially free of plasticizers means, for example, that the blended amount of plasticizer is less than 0.5 parts by mass, preferably 0.3 parts by mass or less, and more preferably 0.1 parts by mass or less, per 100 parts by mass of the polyamide resin contained in the fiber of the present embodiment. By adopting such a configuration, the effects of the present invention tend to be more effectively exhibited. In addition, the fiber of the present embodiment can be given any surface property by performing plasma treatment. For details, refer to the descriptions of paragraphs 0019 to 0022 of JP-A-06-182195, the contents of which are incorporated herein by reference.

[0022] <Stretching> The fiber of the present embodiment may or may not be stretched, but is preferably stretched. By being stretched, there is a tendency that a fiber having superior strength is obtained. The stretching is preferably in the longitudinal direction of the fiber (fiber length direction). In addition, the stretching may be in one stage or in two or more stages, but is preferably in two stages. The stretching ratio (total stretching ratio) is preferably 2.5 times or more, more preferably 3.0 times or more, even more preferably 3.5 times or more, even more preferably 4.0 times or more, even more preferably 4.5 times or more, and even more preferably 5.0 times or more. The upper limit of the stretching ratio is preferably 8.0 times or less, more preferably 7.5 times or less, even more preferably 7.0 times or less, even more preferably 6.5 times or less, even more preferably 6.0 times or less, and even more preferably 5.5 times or less.

[0023] <Fiber characteristics and properties> The fiber of the present embodiment is preferably biodegradable. Biodegradability refers to the ability to be ultimately decomposed into water and carbon dioxide by microorganisms, and includes, for example, those in which a decrease in molecular weight is observed when stored for a certain period of time in a compost environment. The fiber of this embodiment preferably has a biodegradability of 10% or more, more preferably 15% or more, even more preferably 21% or more, even more preferably 25% or more, even more preferably 30% or more, and even more preferably 35% or more after storage for 90 days in a compost environment at 58±2°C and 100% relative humidity. The upper limit of the biodegradability is ideally 100%, but for example, 80% or less, or even 70% or less will be sufficient to meet the required performance. Here, the biodegradability (%) is [(total CO2 generation during storage for 90 days in a compost environment) / (theoretical carbon dioxide generation calculated from the composition formula)]×100. Details are as described in the Examples.

[0024] The length (mass average length) of the fibers in this embodiment is not particularly limited, but is usually 2 cm or more, preferably 0.1 m or more, more preferably 1 m or more, and even more preferably 100 m or more. The upper limit of the fiber length (mass average length) is preferably 20,000 m or less, more preferably 1,000 m or less, and even more preferably 100 m or less.

[0025] The fiber of the present embodiment may be either a monofilament or a multifilament, but is preferably a multifilament, which not only makes it easier to process into various molded articles, but also tends to biodegrade more effectively since the single fiber count of the multifilament is finer than that of the monofilament. When the filament of this embodiment is a multifilament, the number of filaments constituting one multifilament is preferably 10 or more, more preferably 20 or more, and may be 30 or more. The upper limit of the number of filaments constituting one multifilament is preferably 100 or less, more preferably 60 or less, and even more preferably 55 or less. By setting the number within such a range, fusion between single yarns during spinning can be effectively prevented. When forming a multifilament, a sizing agent may be used. The type of sizing agent is not particularly limited as long as it has the function of bundling polyamide resin fibers, but examples include oils such as mineral oil and animal / vegetable oil, nonionic surfactants, anionic surfactants, and amphoteric surfactants. More specifically, ester compounds, alkylene glycol compounds, polyolefin compounds, phenyl ether compounds, polyether compounds, silicone compounds, polyethylene glycol compounds, amide compounds, sulfonate compounds, phosphate compounds, carboxylate compounds, and combinations of two or more of these are preferred. The amount of the sizing agent is preferably 0.1 to 5.0 parts by mass per 100 parts by mass of the fibers.

[0026] The lower limit of the fiber fineness (single fineness) of the present embodiment is preferably 50d (denier) or more, more preferably 100d or more, even more preferably 300d or more, even more preferably 500d or more, and even more preferably 600d or more. The upper limit is preferably 1500d or less, more preferably 1300d or less, even more preferably 1200d or less, and even more preferably 1100d or less. The fineness is measured by the method described in the Examples below.

[0027] The cross section of the fiber of this embodiment is usually circular. Here, circular means not only circular in the mathematical sense, but also includes shapes that are generally considered to be circular in the technical field of this embodiment. The cross section of the fiber of this embodiment may be a shape other than circular, for example, a flat shape such as an ellipse or an oval.

[0028] The linear strength of the fiber of this embodiment is preferably 3.0 gf / d or more, more preferably 3.5 gf / d or more, even more preferably 4.0 gf / d or more, and may be 4.5 gf / d or more, particularly 5.0 gf / d or more. By making it equal to or more than the lower limit, the effect of preventing breakage due to load in the tensile direction of the fiber tends to be improved. The upper limit of the linear strength of the fiber of this embodiment is not particularly determined, but the required performance is satisfied even if it is, for example, 10.0 gf / d or less, further 8.0 gf / d or less, particularly 7.0 gf / d or less.

[0029] The knot strength of the fiber of this embodiment is preferably 2.0 gf / d or more, more preferably 2.5 gf / d or more, even more preferably 3.0 gf / d or more, and may be 3.5 gf / d or more, particularly 3.8 gf / d or more. By making it equal to or more than the lower limit, for example, the effect of suppressing breakage at knots in fishing net applications tends to be improved. The upper limit of the knot strength of the fiber of this embodiment is not particularly determined, but the required performance is satisfied even if it is, for example, 8.0 gf / d or less, further 6.0 gf / d or less, particularly 7.0 gf / d or less. The linear strength and knot strength are measured by the method described in the Examples below.

[0030] <Manufacturing method> The fiber of the present embodiment is obtained by molding a composition containing a polyamide resin and a cobalt salt. The molding method is arbitrary, and the fiber may be molded into a desired shape by any conventionally known molding method such as melt spinning. For example, the description in paragraphs 0051 to 0058 of International Publication No. 2017 / 010389 can be referred to, and the contents of these paragraphs are incorporated herein by reference. The molding conditions and the shape after molding may be appropriately selected and determined depending on the application, and may be changed appropriately for example for fishing net fibers, fishing line fibers, industrial material fibers, woven fabric fibers for clothing, carpets, etc., racket strings, etc.

[0031] <Application> The fiber of the present embodiment may be used as it is, or may be processed into filamentary materials such as blended yarns, braids, twisted cords, etc. Also, it is preferably used as a molded product such as a woven fabric, knitted fabric, nonwoven fabric, etc. Furthermore, the molded product may be a finished product, a part, or a material to be further processed. The fibers of the present embodiment may be wound around a core material, i.e., a wound body having a core material and the fibers wound around the core material may be formed. The fiber or molded body of the present embodiment is widely used in transportation machine parts such as automobiles, general machine parts, precision machine parts, electronic and electrical equipment parts, OA equipment parts, building materials and housing-related parts, medical devices, leisure and sports supplies (e.g., fishing lines), agricultural and forestry products, toys, medical products, food packaging films, daily necessities such as clothing, defense and aerospace products, etc. In particular, since the fiber or molded body of the present embodiment is excellent in biodegradability, it is preferably used for filter cloths, leisure and sports supplies (e.g., fishing lines), and fishing nets, and more preferably used for fishing nets. The fiber of the present embodiment and the molded body of the present embodiment can be discarded by being biodegraded. The fiber and molded body of the present embodiment can be decomposed to the molecular level by the action of microorganisms and finally become carbon dioxide and water and be recycled into the natural world. Therefore, it is beneficial in that it can be discarded in nature without damaging nature. That is, in this specification, a method for discarding fibers including biodegradation of the fiber or molded body of the present embodiment is also disclosed.

Examples

[0032] The present invention will be described more specifically with reference to the following examples. The materials, amounts used, ratios, treatment contents, treatment procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. When the measuring instruments, etc. used in the examples are difficult to obtain due to being out of production, etc., measurements can be made using other devices having equivalent performance.

[0033] 1. Raw materials <Synthesis example of MXD10> Into a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping funnel, and a nitrogen gas inlet tube, 60.00 mol of sebacic acid weighed accurately was charged. After sufficient nitrogen substitution, the temperature was raised to 170 °C under a slight nitrogen stream to dissolve the sebacic acid and make it into a uniform fluid state. To this, 60 mol of metaxylene diamine was added dropwise with stirring over 160 minutes. During this time, the pressure inside the reaction system was kept at atmospheric pressure, and the internal temperature was continuously raised to 250 °C. The water distilled out along with the dropping of metaxylene diamine was removed outside the system through the partial condenser and the cooler. After the dropping of metaxylene diamine was completed, the reaction was continued for 10 minutes while maintaining the liquid temperature at 250 °C. Then, the pressure inside the reaction system was continuously reduced to 600 Torr over 10 minutes, and then the reaction was continued for 20 minutes. During this time, the reaction temperature was continuously raised to 260 °C. After the reaction was completed, the inside of the reactor was pressurized with nitrogen gas to 0.3 MPa, and the polymer was taken out as a strand from the nozzle at the bottom of the polymerization tank, cut into pellet form after water cooling, and pellets of the melt-polymerized product were obtained. These pellets were dried in a vacuum dryer at 150 °C for 5 hours. The melting point measured according to the DSC of the obtained polyamide resin (MXD10) was 191 °C. The mass ratio of the xylylenediamine structure is 44.4 mass%.

[0034] <Synthesis Example of PXD10> Into a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping funnel, and a nitrogen gas inlet tube, 60.00 mol of sebacic acid weighed accurately was charged. After sufficient nitrogen substitution, the temperature was raised to 170 °C under a small amount of nitrogen flow to dissolve the sebacic acid and make it into a uniform fluid state. To this, 60 mol of p-xylylenediamine was added dropwise with stirring over 160 minutes. During this time, the internal pressure of the reaction system was kept at atmospheric pressure, and the internal temperature was continuously raised to 285 °C. The water distilled out along with the dropwise addition of p-xylylenediamine was removed outside the system through the partial condenser and the cooler. After the dropwise addition of p-xylylenediamine was completed, the reaction was continued for 10 minutes while maintaining the liquid temperature at 290 °C. Then, the internal pressure of the reaction system was continuously reduced to 600 Torr over 10 minutes, and then the reaction was continued for 20 minutes. During this time, the reaction temperature was continuously raised to 305 °C. After the reaction was completed, the inside of the reactor was pressurized with nitrogen gas to 0.3 MPa, and the polymer was taken out as a strand from the nozzle at the bottom of the polymerization tank. After water cooling, it was cut into pellet form to obtain pellets of the melt-polymerized product. These pellets were dried in a vacuum dryer at 150 °C for 5 hours. The melting point measured according to the DSC of the obtained polyamide resin (PXD10) was 290 °C. The mass ratio of the xylylenediamine structure is 44.4 mass%.

[0035] <Synthesis Example of MXD12> Into a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping funnel, and a nitrogen gas inlet tube, 60.00 mol of accurately weighed 1,12-dodecanedioic acid was charged, and it was thoroughly purged with nitrogen. Then, while maintaining a small nitrogen gas flow, the temperature was raised to 180 °C to dissolve the 1,12-dodecanedioic acid to form a uniform flowing state. To this, 60 mol of metaxylylenediamine was added dropwise with stirring over 160 minutes. During this period, the internal pressure of the reaction system was maintained at atmospheric pressure, and the internal temperature was continuously raised to 250 °C. The water distilled off along with the dropwise addition of metaxylylenediamine was removed outside the system through the partial condenser and the cooler. After the dropwise addition of metaxylylenediamine was completed, the reaction was continued for 10 minutes while maintaining the liquid temperature at 250 °C. Then, the internal pressure of the reaction system was continuously reduced to 600 Torr over 10 minutes, and then the reaction was continued for 20 minutes. During this period, the reaction temperature was continuously raised to 260 °C. After the reaction was completed, the inside of the reactor was pressurized with nitrogen gas to 0.3 MPa, and the polymer was taken out as a strand from the nozzle at the bottom of the polymerization tank. After water cooling, it was cut into pellet form to obtain pellets of the melt-polymerized product. The obtained pellets were charged into a tumbler (rotary vacuum tank) having a jacket heated by a heat medium at room temperature. While rotating the tumbler, the inside of the tank was evacuated to a reduced pressure state (0.5 - 10 Torr), the circulating heat medium was heated to 150 °C, the pellet temperature was raised to 130 °C, and it was held at that temperature for 3 hours. Then, nitrogen was introduced again to return to atmospheric pressure, and cooling was started. When the temperature of the pellets dropped below 70 °C, the pellets were taken out of the tank to obtain a solid-phase polymerized product. The melting point measured according to the DSC of the obtained polyamide resin (MXD12) was 190 °C. The mass ratio of the xylylenediamine structure was 40.6 mass%.

[0036] <Synthesis Example of MP12> Into a jacketed reactor equipped with a stirrer, a partial condenser, a cooler, a thermometer, a dropping funnel, and a nitrogen gas inlet tube, 60.00 mol of accurately weighed 1,12-dodecanedioic acid was placed, and it was thoroughly purged with nitrogen. Then, while maintaining a small flow of nitrogen gas, the temperature was raised to 180 °C to dissolve the 1,12-dodecanedioic acid and achieve a uniform fluid state. To this, 60 mol of para / methaxylylenediamine, with 40 mol% of the diamine component being para-xylylenediamine and 60 mol% being meta-xylylenediamine, was added dropwise with stirring over 160 minutes. During this time, the internal pressure of the reaction system was maintained at atmospheric pressure, and the internal temperature was continuously raised to 250 °C. Also, the water distilled out during the dropwise addition of para / methaxylylenediamine was removed outside the system through the partial condenser and the cooler. After the dropwise addition of para / methaxylylenediamine was completed, the reaction was continued for 10 minutes while maintaining the liquid temperature at 250 °C. Then, the internal pressure of the reaction system was continuously reduced to 600 Torr over 10 minutes, and then the reaction was continued for 20 minutes. During this time, the reaction temperature was continuously raised to 260 °C. After the reaction was completed, the inside of the reactor was pressurized with nitrogen gas to 0.3 MPa, and the polymer was taken out as a strand from the nozzle at the bottom of the polymerization tank. After water cooling, it was cut into pellet form to obtain pellets of the melt-polymerized product. The obtained pellets were charged into a tumbler (rotary vacuum tank) having a jacket heated by a heat medium at room temperature. While rotating the tumbler, the inside of the tank was evacuated to a reduced pressure state (0.5 - 10 Torr), the circulating heat medium was heated to 150 °C, the pellet temperature was raised to 130 °C, and held at that temperature for 3 hours. Then, nitrogen was introduced again to return to atmospheric pressure, and cooling was started. When the temperature of the pellets reached 70 °C or lower, the pellets were taken out of the tank to obtain a solid-phase polymerized product. The melting point measured according to the DSC of the obtained polyamide resin (MP12) was 216 °C. The mass ratio of the xylylenediamine structure was 40.6 mass%.

[0037] <Synthesis Example of MXD20> In the above synthesis example of MP12, it was synthesized in the same manner except that 100 mol% of the diamine component was meta-xylylenediamine and 1,12-dodecanedioic acid was changed to 1,20-eicosanedioic acid. The melting point measured according to the DSC of the obtained polyamide resin (MXD20) was 168 °C. The mass ratio of the xylylenediamine structure is 30.3 mass %.

[0038] Cobalt stearate (StCo): Kanto Chemical Co., Ltd., product number: 07423-02

[0039] 2. Examples 1 to 5 and Comparative Examples 1 to 5 <Textile manufacturing> The polyamide resin and cobalt stearate were weighed and blended in a tumbler so as to obtain the composition shown in Table 1 or Table 2 described later. The mixture was melted using a single-screw extruder and spun through a spinneret at a spinning temperature of the melting point of the polyamide resin + 20°C. The mixture was taken up in a water bath at a temperature of 50°C and continuously stretched without being taken up once. The stretching was performed in two stages and one stage of heat setting, and a 75°C hot water bath was used in the first stage stretching zone and a 180°C dry hot air bath was used in the second stage stretching zone as the stretching means. The stretching conditions were a total stretch ratio of 3 to 4.5, a second stage stretch ratio of 1.0 to 1.5, and a relaxation rate of 5%, as shown in Table 1 or Table 2, to obtain a fiber (monofilament).

[0040] <Fineness> The fineness (positive weight fineness) of each fiber in the dry state was measured according to the standard of JIS L 1013:2010. The unit is denier (d).

[0041] <Straight line strength> The linear strength of the dry fibers was measured in accordance with JIS L 1013: 2010. The unit of linear strength is gf / d.

[0042] <Knot strength> The knot strength of the dry fibers was measured according to JIS L 1013: 2010. The unit of knot strength is gf / d.

[0043] <Biodegradability> Biodegradability was measured according to JIS K 6953-1 (aerobic compost biodegradation test method). 10 g of fiber was mixed with 60 g of compost with a dry mass of 45 to 50% by mass. This mixture was placed in a compost environment at 58 ± 2°C and 100% relative humidity, and the air was saturated with water and gas with carbon dioxide removed was aerated, and a biodegradation test was performed for 90 days. The amount of carbon dioxide generated was measured, and the biodegradability was calculated from the total theoretical amount of carbon dioxide generated according to the following formula. Biodegradability (%) = [(total amount of CO2 generated during storage for 90 days in a compost environment) / (total amount of theoretical carbon dioxide generated)] x 100 The total theoretical amount of carbon dioxide generated was calculated according to the following formula using the total organic carbon (TOC) amount of the test material previously measured with a CHN analyzer and the sample weight of 10 g. Theoretical amount of carbon dioxide generated (g) = [(total organic carbon (TOC) of test material / 100] x 3.67 x 10 The compost was measured using a Yawata Bussan YK-11. The amount of carbon dioxide was measured using a non-dispersive infrared analyzer (LI-COR LI-830). The CHN analyzer was PerkinElmer PE2400 Series II.

[0044] [Table 1]

[0045] [Table 2]

[0046] The blending amount in the StCo column in Tables 1 and 2 above is shown as the amount of cobalt atoms in the amount of cobalt stearate relative to 100 parts by mass of polyamide resin. As is clear from the above results, the fibers of the present invention were excellent in biodegradability (Examples 1 to 5). In particular, as is clear from comparisons between Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, Example 4 and Comparative Example 4, and Example 5 and Comparative Example 5, before biodegradation, the fibers had strength equivalent to that of fibers not containing cobalt salts and not excellent in biodegradability.

Claims

1. Contains polyamide resin and cobalt salt, The polyamide resin includes a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and includes a xylylenediamine-based polyamide resin in which 50 mol % or more of the diamine-derived structural units are derived from xylylenediamine and 50 mol % or more of the dicarboxylic acid-derived structural units are derived from an α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms. A fiber, The fiber has a plasticizer content of less than 0.5 parts by mass based on 100 parts by mass of the polyamide resin.

2. The fiber according to claim 1, wherein the mass ratio of the xylylenediamine structure in the xylylenediamine-based polyamide resin is 20 to 70 mass%; here, the mass ratio of the xylylenediamine structure is a value calculated by [(mass of the xylylenediamine structure in the polyamide resin) / (total mass of the polyamide resin)]×100.

3. The fiber according to claim 1 or 2, wherein the α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms includes an α,ω-linear aliphatic dicarboxylic acid having 11 to 22 carbon atoms.

4. The fiber according to claim 1 or 2, wherein the α,ω-linear aliphatic dicarboxylic acid having 8 to 22 carbon atoms includes 1,12-dodecanedioic acid.

5. The fiber of any one of claims 1 to 4, wherein the cobalt salt comprises a carboxylate of cobalt.

6. The fiber of any one of claims 1 to 4, wherein the cobalt salt comprises cobalt stearate.

7. The fiber according to any one of claims 1 to 6, wherein the content of cobalt atoms in the cobalt salt is 10 to 2000 ppm by mass relative to 100 parts by mass of the xylylenediamine-based polyamide resin.

8. The fiber according to any one of claims 1 to 7, which is biodegradable.

9. The fiber according to any one of claims 1 to 8, wherein the fiber has a biodegradability of 10% or more after storage for 90 days in a compost environment at 58±2°C and 100% relative humidity. Here, the biodegradability (%) is [(total CO 2 The theoretical amount of carbon dioxide generated calculated from the composition formula is calculated as follows:

10. A molded article formed from the fiber according to any one of claims 1 to 9.

11. The molded article according to claim 10, wherein the molded article is a fishing net.

12. A method for disposing of fibers, comprising biodegrading the fibers according to any one of claims 1 to 9.

13. A method for disposing of a molded article, comprising biodegrading the molded article according to claim 10 or 11.

Citation Information

Patent Citations

  • Method for producing biodegradable polymer composition

    JP2002542313A

  • Polyamide filament

    JP2010281027A

  • Monofilament

    JP2016223037A

  • Multilayer container and method for producing recycled polyester

    JP2018043773A

  • Resin composition, molding, fiber and film

    JP2019026686A